Gaming Activities and Forest Resources Degradation in Obubra Local Government Area of Cross River State - USANG, Nkanu Onnoghen; UNIMTIANG, Unimke Sylvanus; NWAGBARA, Moses; USANG, Rose Onnoghen; MICHAEL, Prince Isong (Ilorin Journal of Education, 2024)
This study investigates the relationship between gaming activities and forest resources degradation in Obubra Local Government Area of Cross River State. To achieve the purpose of this study, two research questions and two null hypotheses were formulated. Correlational research design was adopted for the study. The area of the study was Obubra LGA, Cross River State. The target population was all household members who are farmers aged 18 to 35 years. Multistage sampling techniques were adopted in selecting four hundred and fifty (450) respondents used for the study. A ten item modified four point Likert scale questionnaire titled "Gaming activities and Forest Resources Degradation Questionnaire (GAFRCQ)" was the instruments used for collecting data for the study. To test the hypothesis formulated for the study, Pearson product moment correlation statistical tools was used as statistical tool for data analysis. The hypotheses formulated were tested at 0.05 level of significance. The statistical report of research question one established that there are several gaming activities taking place in the study area. The report in research question two established that forest resources degradation are available in the study Area. The results of the analysis revealed that there is a significant relationship between hunting for sport and forest resources degradation. There is a significant relationship between hunting for bush meat and forest resources degradation. Based on the findings it was recommended among others that the government and other environmental stakeholders should ensure that community dwellers participate on mobilization and awareness against unsustainable gaming activities.